2022
DOI: 10.3390/insects13090827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parental Age and Mating Status on Reproductive Performance of Orius laevigatus (Hemiptera: Anthocoridae)

Abstract: The reproductive potential of biological control agents (BCAs) is crucial for efficient mass-rearing and field performance, and it all begins with mating. Fecundity can be strongly influenced by intrinsic conditions, such as female age and, often neglected, male age and mating status. However, little is known about the impact of parental status at mating on female reproductive outcomes in BCAs. Orius laevigatus (Fieber) (Hemiptera: Anthocoridae) is widely used to control thrips in protected crops. We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The duration of mating also has a direct impact on the reproductive success of insects. In Macrolophus caliginosus and Orius laevigatus , there was no correlation between fecundity and duration of mating 36,37 . In Dysdercus koenigii , Togo hemipterus and Nysius huttoni , however, researchers found that fecundity was positively correlated with the duration of mating 38–40 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The duration of mating also has a direct impact on the reproductive success of insects. In Macrolophus caliginosus and Orius laevigatus , there was no correlation between fecundity and duration of mating 36,37 . In Dysdercus koenigii , Togo hemipterus and Nysius huttoni , however, researchers found that fecundity was positively correlated with the duration of mating 38–40 .…”
Section: Discussionmentioning
confidence: 96%
“…In Macrolophus caliginosus and Orius laevigatus, there was no correlation between fecundity and duration of mating. 36,37 In Dysdercus koenigii, Togo hemipterus and Nysius huttoni, however, researchers found that fecundity was positively correlated with the duration of mating. [38][39][40] Sublethal exposure to imidacloprid in E. heros enhanced the duration of mating and resulted in increased fecundity.…”
Section: Discussionmentioning
confidence: 99%